EVALUATION OF RESISTANCE TO BETA-LACTAM ANTIMICROBIALS IN STRAINS OF WILD ESCHERICHIA COLI, BW535 MUTANT OF CLINICAL ORIGIN CHALLENGED WITH MENADIONE - Graça dos Santos, Juliana; Ribeiro Bello, Alexandre; Cláudia de Paula Ignácio, Ana (Health and Society, 2023)
The Enterobacteriaceae family is one of the main groups of infectious agents that presents mechanisms of resistance to antimicrobials, including broad-spectrum ones such as carbapenem beta-lactams. Previous studies have reported the possibility that oxidative stress, which means the imbalance between the oxidative challenge and the body’s antioxidant defense capacity, is aligned with antimicrobial resistance. The body has a complex system of antioxidant protection, as a defense mechanism against free radicals, which are constantly formed in normal cellular metabolism and in various pathogenic events and, when in excess, can cause the oxidation of biological molecules. Free radicals whose unpaired electron is centered on oxygen or nitrogen atoms are called ROS (reactive oxygen species and ERNs (reactive nitrogen species) that can originate from exogenous oxidizing agents such as menadione. This quinone increases in cells the levels of ROS inducing the production of superoxide (SOD) and hydrogen peroxide (H2O2) which can cause cell death.However, bacteria have several defense mechanisms against ROS that play an important role in maintaining physiology. bacteria respond to oxidative stress with expression coordinated by multiple genes. In particular, the SoxRS regulons of Escherichia coli which are composed of genes that are encoded by products that provide resistance to stress to superoxide. In this work we will evaluate in strains of wild E.coli AB1157 , Base Excision Repair (BER) deficient mutant, and samples isolated from clinical material to possible resistance to antimicrobials and menadione.